PO62 | Management of anticoagulation during extracorporeal circulation in a patient with APS (Bleeding, Thrombosis and Vascular Biology)
Background and Aims: Antiphospholipid syndrome is an autoimmune disorder characterized by thrombotic phenomena and obstetric complications, often associated with Systemic Lupus Erythematosus. It is well known that during the natural history of the disease, a thrombotic, non-bacterial form of endocarditis could affect patients (Libman-Sacks endocarditis), and surgical treatment is recommended in cases of valvular dysfunction. During extracorporeal circulation, these patients may require higher levels of anticoagulation with unfractionated heparin to obtain and maintain an ACT level >500 sec, thus avoiding thrombotic complications.